Investigating the relationship between e-tourism ethics and e-revisit intentions: The mediating roles of e-satisfaction and e-web trust - Shakeel Basheer; Sheezan Farooq; Mudasir Ahmad Mir; Viana Hassan (Tourism, 2025)
The emergence of e-tourism in the current digital era has completely changed how people plan their trips and enjoy their entire trip. The goal of the current study is to ascertain how e-tourism ethics and e-revisit intentions are related. Additionally, the current study examines how e-web trust and e-satisfaction mediate this association. Based on previous research, a pilot study was conducted to evaluate the validity and reliability of a questionnaire that was created from the body of existing literature and given to the respondents. Using a descriptive strategy, the study employed an approach that involved analysing a sample of 420 questionnaires. Convenience sampling was used to collect data from respondents, and SPSS version 20 was used for data analysis. AMOS software and the structural equation modelling (SEM) approach were used to assess the assumptions. The investigation’s findings indicated that e-tourism ethics and e-revisit intentions were positively correlated. Additionally, the results of the study demonstrated the mediating impacts of e-web trust and e-satisfaction by demonstrating a strong indirect influence. For those involved in e-tourism enterprises looking to build long-lasting relationships with their online travel clientele, the insights provide valuable information.